Relapsing Syndrome of Inappropriate Antidiuretic Hormone Production Responding to Tolvaptan Treatment in a Patient With a Micronodular Formation of the Posterior Pituitary Gland - Reinke, Lennart M.; Seoudy, Anna Katharina; Gärtner, Friedericke; Rohmann, Nathalie; Schulte, Dominik M.; Schreiber, Stefan; Jansen, Olav; Laudes, Matthias (Experimental and Clinical Endocrinology & Diabetes, 2023)
The syndrome of inappropriate ADH-secretion (SIADH) is a common cause of low sodium levels with diverse aetiology. Here, we report a case of a 41 years old male patient diagnosed with SIADH and a good response to Tolvaptan therapy. Of interest, as a potential unique cause, magnetic resonance imaging revealed a micronodular structure in the posterior pituitary, while no other common cause of SIADH could be identified. Hence, to the best of our knowledge, this is the first case of a Tolvaptan-responsive SIADH associated with a pituitary micronodular structure.